2019
DOI: 10.4025/jphyseduc.v30i1.3014
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Physical Exercise at different intensities on Inflammatory Markers in Obese Adolescents

Abstract: Obesity promotes a state of chronic low-grade inflammation of white adipose tissue, which is associated with different chronic diseases. While exercise induces an anti-inflammatory environment, little is known about the acute effects of continuous exercise at different intensities on inflammatory markers in obese adolescents. This study included 10 obese adolescents of both sexes, between 15 and 18 years of age. Volunteers performed two 30-minute exercise sessions. The 1st exercise session was performed at mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This study revealed that the TNF-α control group had more significant decrease compared to the experimental group. This finding is in accordance with the previous study by Dos Santos (2019) on obese female adolescents with sedentary behavior who were given a 30-minute intervention with an intensity equivalent to 75% of their treadmill VO2max. The insignificant decrease in TNF-α is associated with exercise intensity that is probably too high for the subjects.…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed that the TNF-α control group had more significant decrease compared to the experimental group. This finding is in accordance with the previous study by Dos Santos (2019) on obese female adolescents with sedentary behavior who were given a 30-minute intervention with an intensity equivalent to 75% of their treadmill VO2max. The insignificant decrease in TNF-α is associated with exercise intensity that is probably too high for the subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Muñoz-Cánoves et al (2013) stated that IL-6 signalling has been associated with stimulation of muscle hypertrophy and myogenesis through regulation of the proliferative capacity of muscle stem cells. Santos et al (2019) in his research using obese adolescent subjects who were given an exercise intervention for 30 min, stated that there was a significant increase in IL-6 levels (P≤0.05). Similar results with this study in relation to TNF-α parameters have been carried out by Mauer et al (2014) who demonstrated a low-grade inflammatory effect by administering a low dose of Escherichia coli endotoxin (0.06 ng/kg) to healthy volunteers, who were randomised to rest or exercise prior to infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The response of vascular inflammatory markers to aerobic exercise depends on exercise duration and intensity. Although a single bout of exercise increased circulating levels of IL-6, -8, -10, tumor necrosis factor-α (TNF-α) and C-reactive protein (CRP) [47,48], regular aerobic exercise was associated with decrease in serum concentration of inflammatory markers. A 2-week voluntary wheel running of old mice reduced activation of the proinflammatory transcription factor NF-κB, diminished aortic expression of the proinflammatory cytokines IL-1 and IL-6 and ameliorated NO-mediated endothelium-dependent dilation [49], and an 8-week running protocol in obese rats decreased plasma TNF-α, increased e-NOS protein expression and improved endothelium-dependent relaxation [50].…”
Section: Endothelial Dysfunction and Aerobic Exercisementioning
confidence: 99%